Przestępczość i polityka karna sądów w Czechosłowackiej Republice Socjalistycznej: [Criminality and penal policy of courts in the Socialist Repubblic of Chechoslovakia] (Studia Prawnicze / The Legal Studies, 1983)
The analysis of dynamics and structure of .criminality and penal policy of courts in Czechoslovakia shows that they have been considerably influenced by changes of laws acid social and events.The greatest influence on the dynamics of revealed criminality was exerted by the law No 150 :of 1969 on misdemeanours which increased a general number of persons prosecuted and sentenced for offences from 1/3 to 1i4. Events in the years 1968-1969 also exerted an extensive influence.The level of revealed criminality in Czechoslovakia is relatively high, anyhow, it is higher than in the majority of other socialist states i(in Poland, Bulgaria, Jugoslavia, GDR and Hungary).The 'coefficient of convictions per 100,000 inhabitants in the early part of the '70s was similar to that from the early part of the '50s, which, to a certain degree, reflects the dynamics of convictions during twenty years. In comparison with Bulgaria and Jugoslavia, the coefficient of convictions is at present considerably higher in Czechoslovakia, and in comparison with Poland — similar, and during some years - a little higher.In the structure of criminality the following four types of offences (according to the systematics of the code) are of a fundamental impocrtance:• economic offences,• offences against life and health,• offences against property,.offences comprised in Part V of the penal code called „Serious offences violating the principles of social coexistance".In certain periods offences against law and order (years 1956-1961) and against the republic (1970-1972) played an important role.A penal means most often applied by courts is conditional suspension of the enforcement of penalty of 'deprivation of liberty. In the '60s A was applied towards ever yother sentenced person (it reached its culminating point in 1969) and in the '70s only towards every third person.Another penal measure quite often applied is .deprivation of liberty. In the years 1961-1967 every fourth sentenced person was deprived of liberty, in the years 1968-1969 - every fifth person, and later - every third person. In the '70s not only the frequency +of penalty of 'deprivation of 'liberty increased but also the number of it. It is a result both of changes of the laws and, first of all, increase of repressions.In the years 1975-1979 the coefficient of persons sentenced to the penalty od deprivation 'of liberty per 100,000 inhabitants smounted to 251, in Jugoslavia - to 116, lo. Bulgaria - to 130-150, Hungary - to 147 and in Poland - to 151.In the '60s, on the average, every sixth, and in the '70s - every fifth sentenced person was sentenced to the penalty of corrective work. Since 1971 this penalty has been more and more often applied.Other penalties are not popular in Czechoslovakia, especially fine, in comparison with other socialist states (Hungary, Jugoslavia and Poland).